Bibliography of Flora and Ethnobiology in West Bengal by Sunit Mitra (Bangladesh Journal of Plant Taxonomy, 2012)
Not applicable.DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10949Bangladesh J. Plant Taxon. 19(1): 99, 2012 (June)